Fatty acid composition, cholesterol and fat-soluble vitamins of wild-caught freshwater spiny eel, Mastacembelus simack (Walbaum, 1792) - Harlioglu, A. G.; Yilmaz, O. (Wiley, 2011)
Because of its local commercial value, the proximate nutritional composition, fatty acid composition, cholesterol and fat-soluble vitamins of spiny eel (Mastacembelus simack Walbaum, 1792) were determined in 20 specimens caught in Keban Dam Lake, Elazig, Turkey in September 2009. Moisture, protein, lipid, ash and cholesterol contents of the spiny eel were 75.9, 17.1, 10.9, 1.0% and 52.6 mg per 100 g, respectively. Fatty acid composition showed that total polyunsaturated fatty acids (PUFA) were the highest (37.1%), followed by monounsaturated fatty acids (MUFA, 35.5%) and saturated fatty acids (SFA, 27.4%). The relation between PUFA and SFA (1.35) was comparable to that of some fish species, and PUFA : MUFA : SFA ratio (1.35 : 1.29 : 1) was very close to that recommended by nutritionists. Among the vitamins (A, D, E and K) analyzed, the vitamin E content was highest followed by D, K and A. In conclusion, M. simack is rich in proteins, unsaturated fatty acids and vitamins and low in cholesterol, with a reasonable PUFA : SFA and PUFA : MUFA : SFA ratio as recommended by nutritionists. M. simack can therefore be recommended for human consumption as a good source of nutrition.
Keywords: Ataturk Dam Lake; Fish; Quality; Growth